Opioid Fills for Lumbar Facet Radiofrequency Ablation Associated with New Persistent Opioid Use. (May 2020) - Southren, Daniel L.; Moser, Stephanie; Abu-Amara, Hasan; Lin, Paul; Schack, Amanda A.; Gunaseelan, Vidhya; Waljee, Jennifer F.; Brummett, Chad M.
Abstract : Background: Zygapophyseal (facet) joint interventions are the second most common interventional procedure in pain medicine. Opioid exposure after surgery is a significant risk factor for chronic opioid use. The aim of this study was to determine the incidence of new persistent use of opioids after lumbar facet radiofrequency ablation and to assess the effect of postprocedural opioid prescribing on the development of new persistent opioid use. Methods: The authors conducted a retrospective cohort study using claims from the Clinformatics Data Mart Database (OptumInsight, USA) to identify opioid-naïve patients between 18 and 64 yr old who had lumbar radiofrequency ablation. Patients who had either subsequent radiofrequency ablation 15 to 180 days or subsequent surgery within 180 days after the primary procedure were excluded from the analysis. The primary outcome was new persistent opioid use, defined as opioid prescription fulfillment within the 8 to 90 and 91 to 180 day periods after radiofrequency ablation. The authors then assessed patient-level risk factors for new persistent opioid use. Results: A total of 2, 887 patients met the inclusion criteria. Of those patients, 2, 277 (78.9%) had radiofrequency ablation without a perioperative opioid fill, and 610 (21.1%) patients had the procedure with a perioperative opioid fill. The unadjusted rate of new persistent opioid use was 5.6% (34 patients) in the group with a perioperative opioid fill versus 2.8% (63 patients) for those without an opioid fill. Periprocedural opioid prescription fill was independently associated with increased odds of new persistent use (adjusted odds ratio, 2.35; 95% CI, 1.51 to 3.66; P < 0.001). Conclusions: Periprocedural opioid use after lumbar radiofrequency ablation was associated with new persistent use in previously opioid-naïve patients, suggesting that new exposure to opioids is an independent risk factor for persistent use in patients having radiofrequency ablation for chronic back pain. Opioid prescribing after radiofrequency ablation should be reevaluated and likely discontinued in this population. Abstract : More than one in five opioid-naïve patients filled a prescription for opioid after minimally painful procedures. Patients who filled opioid prescriptions had more than twice the odds of persistent opioid use.Supplemental Digital Content is available in the text.